Enhancing survival of Demodex folliculorum (Acari: Demodecidae) under in vitro condition: Effect of temperature and culture media - Humberto Maldonado; Dary Mendoza; Gloria Garavito; Martha Lizarazo; Luis Escaf; Eduardo Egea (Persian Journal of Acarology)
Demodex spp. are ectoparasites that live on mammal's skin. Demodex folliculorum Simon is important in the pathogenesis of blepharitis and other inflammatory skin diseases; however, the in vitro culture has not been achieved yet. In this study, the effect of temperature and culture medium on the survival of D. folliculorum was determined.  Adult mites were obtained directly from eyelashes of individuals with a clinical diagnosis of Demodex blepharitis. Temperature ranges from 15–25 ℃, and three culture media (RPMI-1640, RPMI-1640 supplemented with human serum, and RPMI-1640 supplemented with fetal bovine serum) were tested. Results showed significant differences in the survival time of D. folliculorum among different treatments.  The maximum survival of mite was 15.20 ± 1.03 days with RPMI-1640 supplemented with human serum at 20 ℃. This result is the longest reported survival time of D. folliculorum under in vitro maintenance conditions. This research presents a refinement of the methods previously reported to develop an in vitro culture of D. folliculorum.